2023
DOI: 10.3390/cancers15235577
|View full text |Cite
|
Sign up to set email alerts
|

Gaps and Opportunities in the Diagnosis and Treatment of Pancreatic Cancer

Miłosz Caban,
Ewa Małecka-Wojciesko

Abstract: Pancreatic cancer is one of the leading causes off cancer-related deaths globally. In Europe, this type of cancer has the lowest survival rate of all cancers. A majority of patients have unresectable or even metastatic disease. In addition, actual therapeutic options are not curative, and surgical treatment is associated with high post-operative morbidity and a lack of uniform translation of surgical success into long-term survival. Moreover, there is no screening for the general population which is recommende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 183 publications
0
2
0
Order By: Relevance
“…A population-based study conducted in Rochester, Minnesota, USA, found that approximately 1 % of participants with new-onset diabetes aged 50 years or older had diabetes secondary to pancreatic cancer. It is early and comprehensive diagnosis, according to Caban M. and Malecka-Wojciesko E., as well as screening of the disease in the general population and directly in highrisk groups with the use of various biomarkers of pancreatic cancer, that will allow to diagnose the pathology before the appearance of distant metastases and apply radical surgical intervention [5].…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study conducted in Rochester, Minnesota, USA, found that approximately 1 % of participants with new-onset diabetes aged 50 years or older had diabetes secondary to pancreatic cancer. It is early and comprehensive diagnosis, according to Caban M. and Malecka-Wojciesko E., as well as screening of the disease in the general population and directly in highrisk groups with the use of various biomarkers of pancreatic cancer, that will allow to diagnose the pathology before the appearance of distant metastases and apply radical surgical intervention [5].…”
Section: Discussionmentioning
confidence: 99%
“…It is also crucial to identify other guiding features from the anamnestic and physical evaluation and predispose promptly the correct imaging modality with adequate timing. Hence, the understanding of the features of pancreatic pain can be a diagnostic opportunity in the clinical setting, particularly for pancreatic cancer [ 15 ].…”
Section: Introductionmentioning
confidence: 99%